Changes in dental caries and sugar intake before and during the conflict in Libya: A natural experiment. Issue 3 (3rd March 2020) - Arheiam, Arheiam A.; Harris, Rebecca Vera; Baker, Sarah R.
Abstract: Objectives: The primary aim of this study was to investigate the impact of reduced sugar consumption on caries experience among 12‐year‐old Libyan schoolchildren during the Libyan conflict, in comparison to preconflict data collected in the same water‐fluoridated setting from a similar age group. A further aim was to investigate the socio‐demographic and behavioural factors which may impact caries levels during the conflict. Methods: A natural experiment in which dental caries data before and during the Libyan conflict, over a 9‐year period, was compared. A cross‐sectional survey was conducted between December 2016 and February 2017 to collect during‐conflict data comparable to preconflict data collected in 2007. A random sample of 1134, 12‐year‐olds were recruited from public schools in Benghazi. Epidemiological examinations were undertaken by three trained examiners to measure dental caries. Questionnaires addressing socio‐demographic and behaviours related to oral health were completed by participants. Data were analysed using SPSS 24, at P  ≤ .05. Results: In the during‐conflict period, caries prevalence was 42.8% and mean DMFT was 1.09 (SD ± 1.57). These figures were significantly lower than the caries prevalence and severity reported in the preconflict group ( P  < .001). Logistic regression analysis indicated that male children, those who frequently consumed sugary drinks, who drank bottled water (low fluoride) and whose fathers had relatively lowly occupations were more likely to have dental caries (all P  < .05). Conclusions: This study indicates that decreased levels of sugar intake during the Libyan conflict are associated with a decline in dental caries prevalence and severity. This provides some support for the notion that reducing sugar intake is still an important factor in caries prevention and control even when fluorides are available in public water and toothpaste.